2020
DOI: 10.3390/foods9050557
|View full text |Cite
|
Sign up to set email alerts
|

When A Combination of Nudges Decreases Sustainable Food Choices Out-of-Home—The Example of Food Decoys and Descriptive Name Labels

Abstract: This paper reports results from three consecutive studies focusing on the comparison of the effectiveness of different nudges and their combinations to increase sustainable food choices out of the home. The nudges compared are the use of descriptive name labels (DNLs) for the most sustainable dish of a choice set (menu) and the decoy effect (DE), created by adding a less attractive decoy dish to a more attractive target dish with the goal of increasing the choice frequency of the target dish. In the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…However, studies that implemented D (Zhou et al, 2019), P/SA combination (McBey et al, 2019) and SA (Piester et al, 2020;Salmivaara and Lankoski, 2019;Slapø and Karevold, 2019) were not statistically significant. One study which utilised P/SA combination (Ohlhausen and Langen, 2020) showed statistical significance with regards to SA but not P, whilst a P/SA combination (Kaljonen et al, 2020) and I/MN/SA combination (Becchetti et al, 2020) illustrated marginal statistical significance, highlighting the potential use of these combinations.…”
Section: Overall Effectiveness Of Nudging Interventions On Sfcmentioning
confidence: 98%
See 1 more Smart Citation
“…However, studies that implemented D (Zhou et al, 2019), P/SA combination (McBey et al, 2019) and SA (Piester et al, 2020;Salmivaara and Lankoski, 2019;Slapø and Karevold, 2019) were not statistically significant. One study which utilised P/SA combination (Ohlhausen and Langen, 2020) showed statistical significance with regards to SA but not P, whilst a P/SA combination (Kaljonen et al, 2020) and I/MN/SA combination (Becchetti et al, 2020) illustrated marginal statistical significance, highlighting the potential use of these combinations.…”
Section: Overall Effectiveness Of Nudging Interventions On Sfcmentioning
confidence: 98%
“…Three studies utilised P/SA combination (McBey et al, 2019;Kaljonen et al, 2020;Ohlhausen and Langen, 2020), applying signage with availability and accessibility to help encourage more SFC. Kaljonen et al (2020) suggested that increasing the availability and accessibility of vegetarian dishes in a buffet line, placing vegetarian dishes at the front, increased sales by 10%.…”
Section: Sustainable Food Choicesmentioning
confidence: 99%
“…Pure DNLs were more efficient in increasing the choice frequency of the more sustainable meal, whereas the decoy effect resulted in decreased choice frequencies. Also of note, regional and sustainable DNLs were favored by consumers [ 15 ].…”
Section: A Synopsis Of Special Issues Researchmentioning
confidence: 99%
“…Thus, in this Special Issue collection “Consumer Preferences and Acceptance of Food Products” we bring together articles which encompass the wide scope of multidisciplinary research and perspectives in the space related to the determination of key factors involved. The articles included can be considered to cover stakeholders in the perception chain, from ‘the Senses’ regarding fundamental interactions [ 10 , 11 , 12 ], on to ‘Physiological responses’ [ 13 , 14 ], ‘Food choice’ itself, [ 15 , 16 ] and on to studies looking at ‘Purchasing decision processes’ [ 17 , 18 ], and finally to key factors in relation to behaviors in the ‘Market itself’ [ 19 ]. Moreover, we include an in-depth review of extrinsic vs. intrinsic factors themselves in a sweetness in beverage context which brings a unique perspective to beverage design for the future [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, company canteens need to know the factors determining consumers' meal choice at business lunches in order to promote their most sustainable dishes to orient the out-of-home catering market towards increased sustainability. Research illustrates that, in general, consumers' eating habits and meal choices can be influenced by different means, such as System 1 nudges (e.g., default options), System 2 nudges (e.g., information or label) or participation activities [4][5][6][7][8][9][10][11][12]. In particular, consumers' eating habits and meal choice are shown to be affected by search attributes (e.g., price, nutritional composition, variety) [9,13,14], experience attributes (e.g., taste, habit) [9,15], credence characteristics (e.g., organic or regional produce) [13,16,17], sociodemographics (e.g., age, gender) [14,18], and time (e.g., convenience, accessibility) [9,15,19] and can be differentiated into product-based and process-based choices [20].…”
Section: Introductionmentioning
confidence: 99%